Stratigraphic Occurrences of Sub-Polar Planktic Foraminifera in Pleistocene Sediments on the Lomonosov Ridge, Arctic Ocean - O’Regan, Matt; Coxall, Helen K.; Cronin, Thomas M.; Gyllencreutz, Richard; Jakobsson, Martin; Kaboth, Stefanie; Löwemark, Ludvig; Wiers, Steffen; West, Gabriel (Frontiers in Earth Science, 2019)
Turborotalita quinqueloba is a species of planktic foraminifera commonly found in the sub-polar North Atlantic along the pathway of Atlantic waters in the Nordic seas and sometimes even in the Arctic Ocean, although its occurrence there remains poorly understood. Existing data show that T. quinqueloba is scarce in Holocene sediments from the central Arctic but abundance levels increase in sediments from the last interglacial period [Marine isotope stage (MIS) 5, 71–120 ka] in cores off the northern coast of Greenland and the southern Mendeleev Ridge. Turborotalita also occurs in earlier Pleistocene interglacials in these regions, with a unique and widespread occurrence of the less known Turborotalita egelida morphotype, proposed as a biostratigraphic marker for MIS 11 (474–374 ka). Here we present results from six new sediment cores, extending from the central to western Lomonosov Ridge, that show a consistent Pleistocene stratigraphy over 575 km. Preliminary semi-quantitative assessments of planktic foraminifer abundance and assemblage composition in two of these records (LOMROG12-7PC and AO16-5PC) reveal two distinct stratigraphic horizons containing Turborotalita in MIS 5. Earlier occurrences in Pleistocene interglacials are recognized, but contain significantly fewer specimens and do not appear to be stratigraphically coeval in the studied sequences. In all instances, the Turborotalita specimens resemble the typical T. quinqueloba morphotype but are smaller (63–125 μm), smooth-walled and lack the final thickened calcite layer common to adults of the species. These results extend the geographical range for T. quinqueloba in MIS 5 sediments of the Arctic Ocean and provide compelling evidence for recurrent invasions during Pleistocene interglacials.